Diagnostic efficacy and clinical utility of whole-exome sequencing in Czech pediatric patients with rare and undiagnosed diseases - Slaba, Katerina; Pokorna, Petra; Jugas, Robin; Palova, Hana; Prochazkova, Dagmar; Aulicka, Stefania; Spanelova, Klara; Danhofer, Pavlina; Horak, Ondrej; Tuckova, Jana; Kleiblova, Petra; Gaillyova, Renata; et al. (Scientific reports, 2024)
In the last decade, undiagnosed disease programs have emerged to address the significant number of individuals with suspected but undiagnosed rare genetic diseases. In our single-center study, we have launched a pilot program for pediatric patients with undiagnosed diseases in the second-largest university hospital in the Czech Republic. This study was prospectively conducted at the Department of Pediatrics at University Hospital Brno between 2020 and 2023. A total of 58 Czech patients with undiagnosed diseases were enrolled in the study. All children underwent singleton WES with targeted phenotype-driven analysis. We identified 28 variants, including 11 pathogenic, 13 likely pathogenic, and 4 VUS according to ACMG guidelines, as diagnostic of genetic diseases in 25 patients, resulting in an overall diagnostic yield of 43%. Eleven variants were novel and had not been previously reported in any public database. The overall clinical utility (actionability) enabling at least one type of change in the medical care of the patient was 76%, whereas the average number of clinical implications to individual patient care was two. Singleton WES facilitated the diagnostic process in the Czech undiagnosed pediatric population. We believe it is an effective approach to enable appropriate counseling, surveillance, and personalized clinical management.
Keywords: Genetic Testing; Male; Child, Preschool; genetické testování; Adolescent; Infant; Česká republika; sekvenování exomu; vzácné nemoci; Child; Whole-exome sequencing; Rare genetic diseases; dítě; Undiagnosed patients; Prospective Studies; mužské pohlaví; mladiství; Czech Republic; novorozenec; předškolní dítě; lidé; ženské pohlaví; Humans; Infant, Newborn; kojenec; Female; Exome Sequencing; Undiagnosed Diseases; nediagnostikované nemoci; Rare Diseases; prospektivní studie